Proceedings of the Seventh Asia International Symposium on Mechatronics Volume I - Duan, Baoyan; Umeda, Kazunori; Hwang, Woonbong (Lecture Notes in Electrical Engineering, 2020)
XVII, 1034 p. 844 illus., 620 illus. in color.